2022
DOI: 10.1186/s40644-022-00492-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the deep learning technique for the diagnosis of orbital invasion on CT in patients with a nasal or sinonasal tumor

Abstract: Background In nasal or sinonasal tumors, orbital invasion beyond periorbita by the tumor is one of the important criteria in the selection of the surgical procedure. We investigated the usefulness of the convolutional neural network (CNN)-based deep learning technique for the diagnosis of orbital invasion, using computed tomography (CT) images. Methods A total of 168 lesions with malignant nasal or sinonasal tumors were divided into a training data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Some studies used AI to differentiate anterior ethmoidal artery location, 20 identify middle turbinate pneumatization (concha bullosa), 21 and recognize and calculate the volume of the inferior turbinate and maxillary sinus 53 . Most studies have combined AI with CT 20,21,35,44,46,47,53,56,69,80 . Other studies have combined AI with MRI, 33,39,40,45 whole‐slide imaging (WSI), 14,15,51 endoscopic images, 82,90 or positron emission tomography (PET)‐CT 34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies used AI to differentiate anterior ethmoidal artery location, 20 identify middle turbinate pneumatization (concha bullosa), 21 and recognize and calculate the volume of the inferior turbinate and maxillary sinus 53 . Most studies have combined AI with CT 20,21,35,44,46,47,53,56,69,80 . Other studies have combined AI with MRI, 33,39,40,45 whole‐slide imaging (WSI), 14,15,51 endoscopic images, 82,90 or positron emission tomography (PET)‐CT 34 …”
Section: Discussionmentioning
confidence: 99%
“…Most applications of AI in rhinology are in diagnosing nasal diseases, including nasal polyps, 14,15,51,82 inverted papilloma, 35,46,90 and other sinonasal tumors 39,69 (Supplemental File 3, available online). Some studies used AI to differentiate anterior ethmoidal artery location, 20 identify middle turbinate pneumatization (concha bullosa), 21 and recognize and calculate the volume of the inferior turbinate and maxillary sinus.…”
Section: Application Of Ai In Rhinologymentioning
confidence: 99%
See 2 more Smart Citations
“…Han et al (2022) automatically identified the differences in the orbital cavernous venous malformations (OCVM) from orbital CT images by training 13 ML models, including support vector machines (SVMs) and random forests. Nakagawa et al (2022) implemented a VGG-16 network to determine from CT images whether a nasal or sinus tumor invades the periorbital area. The network model achieved a diagnostic accuracy of 0.920, indicating that CNN-based DL techniques can be a useful supporting tool for assessing the presence of orbital infiltration on CT images.…”
Section: Sabatesmentioning
confidence: 99%